Performance evaluation of solar PV mini grid system in Nepal: a case study Thabang and Sugarkhal - Karna, Sanjay Lal; Jha, Ajay Kumar; Yadav, Kishori; Kumar Mallik, Jiwan (Frontiers in Energy Research, 2024)
This article investigates the performance metrics of two solar mini-grid systems, Thabang Solar Mini-Grid (TSMG) and Sugarkhal Solar Mini-Grid (SSMG), based on secondary live data, collected from Renewable Energy for Rural Livelihood (RERL) and PVsyst software 7.4 spanning the years 2021-2023. Notably, the highest irradiance levels were recorded in April for both TSMG and SSMG. TSMG exhibited an energy generation of 83.206 MWh/year in 2021 and 112.140 MWh/year in 2022, with a peak sun hour (PSH) of 5.5h. Conversely, SSMG energy generated 64.14 MWh/year in 2021 and 68.79 MWh/year in 2022, with a PSH of 5.7h. The capture loss of SSGM recorded 0.239 kWh/day to 3.322 kWh/day in 2021 and 0.082 kWh/day to 2.086kWh/day in 2022. Also, the capture loss of TSGM recorded 1.573 kWh/day to 5.011 kWh/day in 2021 and 0.470 kWh/day to 4.261 kWh/day in 2023. The efficiency of SSMG is consistently higher efficiency compared to TSMG. The capture factor of SSMG increased from 9.76% in 2021 to 10.47% in 2022, while of TSMG 6.33% in 2021 to 8.53% in 2023. The findings provide valuable insights into the comparative performance of these solar mini-grid systems, contributing to the optimization and improvement of solar energy generation in diverse environmental conditions.